Eyvind Johnson’s Hybrid North: Dynamics of Place and Time in Travelogues and Memory Sketches 1943–1963 - Thorup Thomsen, Bjarne (Journal of Northern Studies, 2014)
The article explores the depiction and understanding of the Swedish North in memory sketches and travelogues, published between 1943 and 1963, by the author Eyvind Johnson, who was born in 1900 in Svartbjörnsbyn in Sweden’s northernmost county, Norrbotten, and went on to win the Nobel Prize for literature in 1974. The overarching argument of the article is that a creative interplay between places, “traffic,” time and memory in Johnson’s writing shapes a hybrid picture of the Swedish North as a dynamic, inclusive and multidimensional domain, making Johnson’s articulations of the North of heightened relevance today. While frequently preoccupied with the past, Johnson’s representations of the North are always also, explicitly or implicitly, grounded in a contemporary political, economic or environmental context, be it world-war preparedness, welfare development, cold-war crisis, or increased utilisation of natural resources. The article begins by focusing on memory sketches that belong to official anthologies celebrating milestones in the history of administrative structures and demarcations in the North. In these contexts, Johnson operates as an ambassador for the North, while providing incisive, at times critical, perspectives on past and present in the region. Drawing on theories of travel writing as a hybrid and “freer” form of writing, the article goes on to discuss how Johnson in travelogues such as Winter Journey in Norrbotten (1955) and “Summer Diary from Norrbotten” (1963) journeys into contemporary landscapes and townscapes that, at the same time, contain the traces or contours of his personal past. In these texts, Johnson acts both as a child of the North and as a special reporter approaching from the South in order to familiarise external audiences with the region. The article concludes by demonstrating how Johnson in Winter Journey uses contexts and concepts of travel to explore the relationship more broadly between his literary activity and the northern experience. In its finishing argument, the article suggests that notions of hybrid creativity and “transport” of motifs, material and perspectives are key to Johnson’s literary practice and “programme” in relation to the Swedish North.